A Study on the construction of virus infection area information system using IoMT environment - et. al., Sungho Sim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the recent emergence of novel virus, the importance has been empathized on the epidemiologic investigation of the infection route and control of infected patients. Control system on the viral infections is required since the new virus expression cycle becomes faster which was not previously identified with the spread to other regions and countries. Viral infections cause multiple types of problems such as public health, economic and social ones. In addition, viruses can be spread fast beyond the regions and countries all over the world according to the movements of population. Although national quarantine systems have been established to solve these problems by countries, earlier actions on the novel virus were not satisfactory. IoT environment-based healthcare industry and IT convergence medical service industry have been continuously growing. Healthcare IT, which is the area to deal with information on the personal health and medical cares, devices, systems, and platforms, provides with personal healthcare services. In this article, information system on the virus infected territories is proposed using Internet of Medical Things (IoMT) environment. The proposed study is to establish the information system on the virus infected territories by IoMT-based monitoring of infection symptoms for early reactions against the viral infections. The system can be reacted proactively by detecting the risk factors of community spread from early detections of infected patients under the fast spread situation of viral diseases. The information system on the virus infected territories using IoMT environment can react to the spread of infectious diseases actively upon providing the information of infectious disease symptoms using user information. The proposed system can establish the integrative control system of viral diseases by the prediction module of community outbreak and spread of viral diseases.